Perbandingan Proses Pembelajaran Tatap Muka dengan Pembelajaran Daring terhadap Efektifitas Belajar Siswa Kelas XI Akutansi di SMK PGRI 2 Kota Jambi - Mayasari, Mayasari; Kurniadi, Romi; Novita, Sandra; Yaldi, Destri; Muslim, Fachruddiansyah (Jurnal Ilmiah Dikdaya, 2022)
This study aims to compare the face-to-face learning process with online learning on the effectiveness of student learning in class XI Accounting at SMK PGRI 2 Jambi City. The design of this study uses the Quasi Experiment method. The population in this study was 78 students from all XI Accounting Classes at SMK PGRI 2 Jambi City. The sample used in this study consisted of two classes, namely the experimental class (XI AK2) with 26 students and the control class (XI AK1) with 26 students. Data collection techniques used in this study include interviews, observation and multiple choice tests. The research instrument tests used include the validity of the questions and the reliability of the questions, the level of difficulty test, and the test of discriminating power. Furthermore, inferential statistical tests were carried out, namely normality tests and homogeneity tests. The hypothesis test used is the ANCOVA test to answer the research hypothesis. Based on the results of this study, it can be obtained that there is a significant difference between the effectiveness of student learning through the face-to-face learning process and online learning on the learning effectiveness of students in class XI Accounting at SMK PGRI 2 Jambi City. This is evidenced by the calculation of the ancova test listed in the Tests of Between-Subjects Effects table, the significance level in the line "Learning effectiveness" is 0.000 <0.05. Thus, it can be explained that student learning can be said to be effective if mastery learning can be achieved properly through a supportive learning process so that interactions between teachers and students as well as fellow students can spur high enthusiasm for students, so that teachers can create an educative learning atmosphere and conducive.